The Impact of Financial Geographical Structure on Corporate Pollution Emissions - Du, Zhenlan (Transactions on Economics, Business and Management Research, 2023)
This chapter takes a macro perspective on the financial geographical structure, starting from the perspective of financial agglomeration and financial center spillover. Based on the Chinese industrial enterprise database, Chinese pollution emission database, and the China City Statistical Yearbook, it explores the impact of financial geographical structure on corporate pollution reduction. The study finds that local financial agglomeration and financial center spillover can significantly reduce the intensity of corporate pollution emissions, which remains robust after a series of rigorous tests. Mechanism analysis indicates that local financial agglomeration and financial center spillover can promote corporate pollution reduction through the effect of technological innovation. The research conclusions of this chapter can provide new insights for deepening the structural reform of financial supply side.